Diagnosis demam berdarah dengue pada anak - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRAK Dengue haemorrhagic fever (DHF) is one of the most important disease in Indonesia in terms of its morbidity and mortality. The clinical manifestations vary very much. The standard diagnostic criteria consist of 2.7 days fever, bleeding tendency, hepatomegali, shock, hemoconcentration and thrombocytopenia. The presence of any two of the clinical signs together with hemoconcentration and thrombocytopenia is sufficient for diagnosis in practice. This paper discusses the clinical and reporting issues related to these criteria. In relation with the Grade III and Grade IVDHF, i.e. DI-IF with the shock syndrome, has no good prognosis and no clinical sign to predict the syndrome. Therefore, every DHF suspected patient should be monitored intensively.